(untitled) (Medical Forum Monthly, 2024)
Objectives: The objective of this study was to compare the craniofacial measurements with body measurements and their implementation among the Pakistani population. Study Design: Prospective / comparative study Place and Duration of Study: This study was conducted at University College of Dentistry, The University of Lahore from January 2014 to March 2014. Materials and methods: Measurements were taken on 300 fully dentate patients with their teeth in centric occlusion. Results were statistically analyzed by using SPSS version 20. Results: Height of the face to height of the hand, Length of the nose to length of the thumb and Distance from tip of index finger to tip of the thumb and chin-nose distance were measured All these measurements showed a statistically significant p-value thus indicating no correlation with each other. Conclusion: These measurements had no close approximation to each other and with original occlusal vertical dimensions (OVD) among Pakistani population as compared to others races.